Sucrose Acceptance and Different Forms of Associative Learning of the Honey Bee (Apis Mellifera L.) in the Field and Laboratory - Mujagic, Samir; Sarkander, Jana; Erber, Barbara; Erber, Joachim (Frontiers in Behavioral Neuroscience, 2010)
The experiments analyze different forms of learning and 24-h retention in the field and in the laboratory in bees that accept sucrose with either low (≤3%) or high (≥30% or ≥50%) concentrations. In the field we studied color learning at a food site and at the hive entrance. In the laboratory olfactory conditioning of the proboscis extension response (PER) was examined. In the color learning protocol at a feeder, bees with low sucrose acceptance thresholds (≤3%) show significantly faster and better acquisition than bees with high thresholds (≥50%). Retention after 24 h is significantly different between the two groups of bees and the choice reactions converge. Bees with low and high acceptance thresholds in the field show no differences in the sucrose sensitivity PER tests in the laboratory. Acceptance thresholds in the field are thus a more sensitive behavioral measure than PER responsiveness in the laboratory. Bees with low acceptance thresholds show significantly better acquisition and 24-h retention in olfactory learning in the laboratory compared to bees with high thresholds. In the learning protocol at the hive entrance bees learn without sucrose reward that a color cue signals an open entrance. In this experiment, bees with high sucrose acceptance thresholds showed significantly better learning and reversal learning than bees with low thresholds. These results demonstrate that sucrose acceptance thresholds affect only those forms of learning in which sucrose serves as the reward. The results also show that foraging behavior in the field is a good predictor for learning behavior in the field and in the laboratory.